Multicenter Experience with Neurally Adjusted Ventilatory Assist in Infants with Severe Bronchopulmonary Dysplasia - McKinney, Robin L.; Keszler, Martin; Truog, William E.; Norberg, Michael; Sindelar, Richard; Wallström, Linda; Schulman, Bruce; Gien, Jason; Abman, Steven H.; on behalf of the Bronchopulmonary Dysplasia Collaborative (American Journal of Perinatology, 2020)
Objective The aim of this study is to determine patterns of neurally adjusted ventilatory assist (NAVA) use in ventilator-dependent preterm infants with evolving or established severe bronchopulmonary dysplasia (sBPD) among centers of the BPD Collaborative, including indications for its initiation, discontinuation, and outcomes.Study Design Retrospective review of infants with developing or established sBPD who were placed on NAVA after ≥4 weeks of mechanical ventilation and were ≥ 30 weeks of postmenstrual age (PMA).Results Among the 13 sites of the BPD collaborative, only four centers (31%) used NAVA in the management of infants with evolving or established BPD. A total of 112 patients met inclusion criteria from these four centers. PMA, weight at the start of NAVA and median number of days on NAVA, were different among the four centers. The impact of NAVA therapy was assessed as being successful in 67% of infants, as defined by the ability to achieve respiratory stability at a lower level of ventilator support, including extubation to noninvasive positive pressure ventilation or support with a home ventilator. In total 87% (range: 78–100%) of patients survived until discharge.Conclusion We conclude that NAVA can be used safely and effectively in selective infants with sBPD. Indications and current strategies for the application of NAVA in infants with evolving or established BPD, however, are highly variable between centers. Although this pilot study suggests that NAVA may be successfully used for the management of infants with BPD, sufficient experience and well-designed clinical studies are needed to establish standards of care for defining the role of NAVA in the care of infants with sBPD.
Keywords: neurally adjusted ventilatory assist; severe bronchopulmonary dysplasia; mechanical ventilation